(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
CoViD-19 emergency brings to the forefront a subject that has always been little investigated such as clinical trial and administration of off-label drugs. This paper aims to assess, through the analysis of the main measures taken by the Italian and European medicines agencies (AIFA and EMA), the ability of the regulation on the subject to cope with a constantly evolving emergency framework and to respond to several application problems that the exceptional epidemiological situation forces us to face.